2012
DOI: 10.1074/jbc.m111.292847
|View full text |Cite
|
Sign up to set email alerts
|

H2O2-triggered Retrograde Signaling from Chloroplasts to Nucleus Plays Specific Role in Response to Stress

Abstract: Background: Detailed insight into the role of chloroplastic H 2 O 2 in cell signaling is necessary. Results: A large change in gene expression occurred in response to chloroplastic H 2 O 2 , resulting in positive and negative effects on the response to stresses. Conclusion: Chloroplastic H 2 O 2 regulates abiotic and biotic stress response. Significance: We provided a new insight into the role of chloroplastic H 2 O 2 in stress response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
180
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(186 citation statements)
references
References 59 publications
4
180
1
1
Order By: Relevance
“…45 The H 2 O 2 response is defective in guard-cell chloroplasts of the amos1 mutant, independent of external ammonium treatment and the absence or presence of ABA. 31 The expression of H 2 O 2 -responsive genes, such as small heat shock proteins (HSPs), 27,46 is induced greatly in wild-type Arabidopsis, but not in the amos1 mutant, upon exposure to excess ammonium. 31 These data indicate that a chloroplastic ROS signal is a highly plausible candidate for the AMOS1/EGY1-dependent ammonium-induced plastid retrograde signal.…”
Section: Interaction Of Plastid Retrograde Signaling and Aba Signalinmentioning
confidence: 99%
See 4 more Smart Citations
“…45 The H 2 O 2 response is defective in guard-cell chloroplasts of the amos1 mutant, independent of external ammonium treatment and the absence or presence of ABA. 31 The expression of H 2 O 2 -responsive genes, such as small heat shock proteins (HSPs), 27,46 is induced greatly in wild-type Arabidopsis, but not in the amos1 mutant, upon exposure to excess ammonium. 31 These data indicate that a chloroplastic ROS signal is a highly plausible candidate for the AMOS1/EGY1-dependent ammonium-induced plastid retrograde signal.…”
Section: Interaction Of Plastid Retrograde Signaling and Aba Signalinmentioning
confidence: 99%
“…29 Likewise, tAPX regulates the production of H 2 O 2 in chloroplasts. 27 As examples of the second type, plastid EX1 and EX2 proteins are required for the transfer of 1 O 2 -mediated plastid-to-nucleus signaling, although their detailed molecular function is unknown. 20,21 As an example of the third type, transcript profile analysis of flu and flu caa39 mutants revealed that topoisomerase VI (Topo VI) acts as a nuclear component of 1 O 2 -mediated plastid-to-nucleus signaling to directly regulate the expression of the AAA-ATPase and other 1 O 2 -responsive genes.…”
Section: Interaction Of Plastid Retrograde Signaling and Aba Signalinmentioning
confidence: 99%
See 3 more Smart Citations